PENDAMPINGAN MAGANG DALAM RANGKA MENINGKATKAN KOMPETENSI MAHASISWA PADA LEMBAGA FILANTROPI ISLAM - Chasanah, Uswatun; Afandi, Nihro; Mawardi, Imam; Amrullah, A. Afif; Su’eb, Mochammad (MAJU : Indonesian Journal of Community Empowerment, 2024)
An internship is a learning process and/or work practice for students to develop themselves and their knowledge about the world of work. This program serves to introduce students to the world of work. It also increases their competence regarding the theory that students learn in lectures and its application in the world of work. This internship was carried out at two Islamic Philanthropy Institutions in the Surabaya area, namely LAZISNU East Java and Baitul Maal Muamalat (BMM) East Java Representative.  The forms of activities in the two institutions include Fundraising Management, Program Distribution Management, Assistance in Preparing Financial Reports, and Social Media Management. After carrying out internships at these two institutions, students can better understand and have competence regarding Islamic Philanthropy Institutions both in theory and practice